Fermentation weight loss, fermentation quality, and bacterial community of ensiling of sweet sorghum with lactic acid bacteria at different silo densities - Xu, Haiwen; Wu, Nier; Na, Na; Sun, Lin; Zhao, Yi; Ding, Haijun; Fang, Yongyu; Wang, Tianwei; Xue, Yanlin; Zhong, Jin (Frontiers in Microbiology, 2022)
This study aimed to reveal the fermentation weight loss (FWL), fermentation quality, and bacterial community of ensiling sweet sorghum with lactic acid bacterial (LAB; (Lactiplantibacillus plantarum and Lentilactobacillus buchneriand) and different silo density. Sweet sorghum was harvest at the first spikelet of inflorescence just visible stage and ensiled without or with LAB (CK or L) in polyethylene laboratory-scale silos (diameter, 20 cm; height, 30 cm) at densities of 650 kg/m3 (CK_650 and L_650), 700 kg/m3 (CK_700 and L_700), and 750 kg/m3 (CK_750 and L_750), respectively. The FWL, fermentation quality, microbial counts, bacterial community, and aerobic stability of the silage were assessed after 100 d of ensiling. The L_750 had lower FWL than CK_650, _700, and _750 after 100 d of ensiling (P < 0.005) and the FWL was interacted by silo density and inoculating LAB (P < 0.005). All silages had low pH (< 4.0) and ammonia nitrogen (< 50 g/kg total nitrogen) and did not contain propionic and butyric acids; moreover, inoculating LAB increased lactic and acetic acids (P < 0.005). The bacterial communities in inoculated silages and uninoculated silages had clustered together, respectively, and clearly separated from each other. The total abundance of Lactiplantibacillus and Lentilactobacillus in fresh forage was less than 1%. Lactiplantibacillus had the highest abundance in all silage (from 71.39% to 93.27%), followed by Lentilactobacillus (from 3.59% to 27.63%). Inoculating LAB increased the abundance of Lentilactobacillus for each silo density (P < 0.005) and decreased Lactiplantibacillus in the silage with densities of 700 kg/m3 and 750 kg/m3 (P < 0.005); moreover, rising silo density decreased Lactiplantibacillus and increased Lentilactobacillus in inoculated silages (P < 0.005). Overall, the sweet sorghum had satisfactory fermentation quality with no less than a density of 650 kg/m3, and inoculating LAB improve fermentation quality and reduced FWL. Lactiplantibacillus and Lentilactobacillus presented as minor taxa in fresh sweet sorghum and dominated the bacterial community of all silages. Inoculating LAB was main factor affecting the bacterial community of sweet sorghum silage. Moreover, inoculating LAB and rising silo density can contribute to the decreasing Lactiplantibacillus and the increasing Lentilactobacillus for inoculated silage.